2013
DOI: 10.2307/23646334
|View full text |Cite
|
Sign up to set email alerts
|

Has the "Ambition Success Networks" Educational Program Achieved its Ambition?

Abstract: This paper evaluates the French RAR program (Réseaux Ambition Réussite or Ambition Success Networks), a junior high school program started in 2006 which intended to concentrate means and funds on well-chosen disadvantaged junior high schools. We use the criteria of eligibility to estimate a regression discontinuity model. For evaluated junior high schools, the increase in per-pupil teaching hours, and the decrease in class size are disappointing. Our results also suggest that the program may have had a negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
9
0
3
Order By: Relevance
“…In France, Bénabou, Kramarz and Prost (2009) show that the ZEP program had no impact on pupils' achievement. Beffy and Davezies (2013) find a negative impact of the "Réseaux ambition réussite" program on academic achievement. Some reasons may explain why such policies have limited empirical results.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In France, Bénabou, Kramarz and Prost (2009) show that the ZEP program had no impact on pupils' achievement. Beffy and Davezies (2013) find a negative impact of the "Réseaux ambition réussite" program on academic achievement. Some reasons may explain why such policies have limited empirical results.…”
Section: Introductionmentioning
confidence: 76%
“…In a preceding work, Beffy and Davezies (2013) showed that the probability for a school to enter the RAR program increases discontinuously above the 10% and 67% eligibility thresholds. Not every school above the thresholds entered the program and some schools below the thresholds entered it, so the discontinuity is fuzzy.…”
Section: Identificationmentioning
confidence: 93%
“…La publication des modalités de calcul et des budgets réels augmenterait la transparence et forcerait l'administration scolaire et les écoles à mieux rendre des comptes. La réforme de l'éducation prioritaire menée en 2006 n'a pas permis de réduire la taille des classes comme prévu, probablement parce que les recteurs ont usé de leur pouvoir discrétionnaire conséquent pour affecter également des enseignants supplémentaires à des établissements en dehors du réseau prioritaire (Beffy et Davezies, 2013). Or cela pourrait être évité avec une formule de financement et des budgets transparents.…”
Section: Graphique 11 Le Co-enseignement N'est Pas Suffisamment Déveunclassified
“…Les enseignants des établissements classés en REP cumulent plus rapidement des droits qui leurs permettent de choisir une école. Cela incite les enseignants peu expérimentés à rejoindre le réseau d'éducation prioritaire lorsqu'ils ont pour principal objectif d'être transférés dans une autre école (O'Brien, 2007 ;Beffy et Davezies, 2013). Pour accroître l'attractivité des carrières dans l'éducation prioritaire, une meilleure solution consisterait à créer de nouveaux postes d'encadrement intermédiaire pour les bons enseignants et de proposer un accès accéléré à la promotion au poste de chef d'établissement.…”
Section: Graphique 11 Le Co-enseignement N'est Pas Suffisamment Déveunclassified
See 1 more Smart Citation